2013
DOI: 10.2135/cropsci2012.10.0616
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genetic Characterization of a Maize Association Mapping Panel Developed for the Identification of New Sources of Resistance to Aspergillus flavus and Aflatoxin Accumulation

Abstract: Maize (Zea mays L.) susceptibility to ear rot by Aspergillus flavus (Link:Fr) and aflatoxin accumulation causes global economic and human health damage. Host plant resistance is an ideal solution, but commercial varieties lack sufficient resistance to solve the problem. Due to general lack of resistant maize germplasm, no currently available association mapping panels are expected to contain significant variation for the trait. A new association mapping panel containing the majority of aflatoxin accumulation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 55 publications
0
72
0
Order By: Relevance
“…These lines, displaying resistance in at least one field site, are in the process of further characterization. Second, an aflatoxin association mapping panel containing 300 maize lines has recently been publicly released, and 30 to 40 lines displaying good resistance in up to 7 environments are now available for use [33,34]. Several of these inbreds have already been included in a new joint USAID/USDA project, together with two CGIAR centers, to incorporate as many of these lines into ongoing genetics studies and breeding activities as possible, with the goal of creating resistant OPV and hybrid cultivars as quickly as possible.…”
Section: Resistant Germplasmmentioning
confidence: 99%
See 4 more Smart Citations
“…These lines, displaying resistance in at least one field site, are in the process of further characterization. Second, an aflatoxin association mapping panel containing 300 maize lines has recently been publicly released, and 30 to 40 lines displaying good resistance in up to 7 environments are now available for use [33,34]. Several of these inbreds have already been included in a new joint USAID/USDA project, together with two CGIAR centers, to incorporate as many of these lines into ongoing genetics studies and breeding activities as possible, with the goal of creating resistant OPV and hybrid cultivars as quickly as possible.…”
Section: Resistant Germplasmmentioning
confidence: 99%
“…Phenotyping of the panel revealed that the most resistant lines include the previously identified resistant germplasm and many new lines that may now be used for breeding and genetics studies. Pedigrees of a majority of the lines identified as resistant trace back, all or in part, to one Mexican maize landrace, Tuxpeño [33,34]. This landrace has been used extensively in the creation of many of the maize breeding pools and populations of the International Maize and Wheat Improvement Center (CIMMYT) because it is a high yielding, agronomically superior dent population with good GCA.…”
Section: Resistant Germplasmmentioning
confidence: 99%
See 3 more Smart Citations